Star formation in AGN hosts in GOODS-N - Shao, L; Lutz, D; Nordon, R; Maiolino, R; Alexander, D; Altieri, B; Andreani, P; Aussel, H; Bauer, F; Berta, S; Bongiovanni, A; Brandt, W; et al. (2010)
Sensitive Herschel far-infrared observations can break degeneracies that were inherent to previous studies of star formation in high-z AGN hosts. Combining PACS 100 and 160 μm observations of the GOODS-N field with 2 Ms Chandra data, we detect ∼20% of X-ray AGN individually at >3σ. The host far-infrared luminosity of AGN with L2-10 keV ≈ 10 43 erg s-1 increases with redshift by an order of magnitude from z = 0 to z ∼ 1. In contrast, there is little dependence of far-infrared luminosity on AGN luminosity, for L2-10∼ keV 10 44 erg s-1 AGN at z ≳ 1. We do not find a dependence of far-infrared luminosity on X-ray obscuring column, for our sample which is dominated by L2-10∼ keV}}$ < 1044 erg s -1 AGN. In conjunction with properties of local and luminous high-z AGN, we interpret these results as reflecting the interplay between two paths of AGN/host coevolution. A correlation of AGN luminosity and host star formation is traced locally over a wide range of luminosities and also extends to luminous high-z AGN. This correlation reflects an evolutionary connection, likely via merging. For lower AGN luminosities, star formation is similar to that in non-active massive galaxies and shows little dependence on AGN luminosity. The level of this secular, non-merger driven star formation increasingly dominates over the correlation at increasing redshift. © 2010 ESO.